Validity and reliability study of the vaccine hesitancy scale in Turkish sample - Yalnız Dilcen, Hacer; Dolu, İlknur and Turhan, Zeynep (The European Research Journal, 2022)
Objectives: This study aims to test the validity and reliability of the Vaccine Hesitancy Scale (VHS) developed by Larson for Turkish society due to the limited measures of vaccine hesitancy studies in Turkey. This scale can help advance research and vaccination policy for human well-being. Methods: Two hundred fourty-six participants completed the first questionnaire in Turkish between September and October 2020. The sample of the study was determined to consider the number of items on the 9-item scale is more than 27 times. The retest was used to test the validity of the scale in the study. Results: The ratio of the scale to chi-square degrees of freedom is 2.29. This can be considered as a sufficient fit. As a result of the first level Confirmatory Factor Analysis (CFA), the values ​​of the goodness of fit suggested that the two-factor model can be considered compatible with the data. The Cronbach’s alpha of the total items of the scale is = .801. Factor 1 which was the ‘lack of confidence’ of Cronbach’s alpha was 0.904. Factor 2 that was the ‘risks’ was 0.742. The reliability and validity of the VHS analysis revealed a two-factor structure with construct and criterion validity to detect vaccine hesitancy. Conclusions: VHS is recommended to be used as a data collection tool in health care services to detect the level of vaccine hesitancy among the public. The adaptation of VHS into the Turkish language can help health care providers and immunization policy makers to improve effective approaches by focusing on the individuals’ confidence in vaccination.